The in vitro effects of trimethyltin on the androgen biosynthesis of rat immature Leydig cells. (November 2020) - Hu, Jiasheng; Zhang, Dongxu; Yan, Zejun; Cheng, Yue
Abstract: Trimethyltin (TMT) is widely used in industry and agriculture. The present study aims to clarify the effects of in vitro TMT exposure on androgen biosynthesis and metabolism in immature Leydig cells (ILCs), and to unveil the underlying mechanism. It was found that 1-10μM TMT decreased ILC androgen productions under basal conditions. TMT at 10μM decreased luteinizing hormone (LH) or 8-Br-cAMP (8BR)-stimulated androgen productions from ILCs. TMT at 10μM decreased 22R-hydroxycholesterol (22R) and androstenedione (D4)-mediated androgen productions from ILCs. TMT at 0.1-10μM down-regulated the mRNA or protein expression levels of STAR, CYP11A1, 17β-HSD3, or NR5A1. TMT at 10μM directly inhibited the enzyme activities of CYP11A1 and 17β-HSD3. In conclusion, the present study demonstrated that in vitro TMT exposure decreased ILC function of androgen production, via exerting negative effects on the mRNA/protein expression levels, or enzyme activities of STAR, CYP11A1, 17β-HSD3, or NR5A1.